The Effect of Service Quality, Promotion Strategy, and Price Perception on Customer Satisfaction at Adira Finance Singaraja Branch - Lutfi, Aden Winangun; Yudiaatmaja, Fridayana; Suci, Ni Made (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study investigates the impact of service quality, promotional strategies, and price perception on customer satisfaction at Adira Finance, Singaraja Branch. In an increasingly competitive financial services industry, customer satisfaction plays a pivotal role in fostering loyalty and business growth. The research aims to identify how each of these factors influences customer satisfaction, and which factor holds the most significant impact. Data was collected through a survey of 25 respondents, revealing key insights into the effectiveness of service quality, promotional strategies, and pricing strategies. The results indicate that service quality has the most substantial effect on customer satisfaction, followed by promotional strategies and price perception. These findings suggest that companies in the finance sector should focus on improving service quality while integrating effective promotional strategies and maintaining competitive pricing to ensure sustained customer satisfaction. This research contributes to the understanding of customer satisfaction dynamics in the finance sector, providing actionable recommendations for improving service offerings in similar institutions.